Eligibility criteria in private and public coverage policies for BRCA genetic testing and genetic counseling - Wang, Grace (Genet Med, 2011)
PURPOSE: Coverage policies for genetic services for hereditary cancers are of interest because the services influence cancer risk reduction for both persons with cancer as well as their family members. We compared coverage policies for BRCA genetic testing and genetic counseling among selected payers in the US to illuminate eligibility criteria variation that may explain differential access by insurance type. We compared these policies to policies for breast cancer screening with MRI to consider whether payers apply a unique policy approach to genetic services. METHODS: We conducted a case study of large private and public payers selected on number of covered lives. We examined coverage policies for BRCA genetic testing, genetic counseling, and screening with MRI and the eligibility criteria for each. We compared eligibility criteria against National Comprehensive Cancer Network guidelines. RESULTS: Eligibility criteria for BRCA testing were related to personal history and family history of cancer. Although private payers covered BRCA testing for persons with and without cancer, the local Medicare carrier in our study only covered testing for persons with cancer. In contrast, Arizona's Medicaid program did not cover BRCA testing at all. Few payers had detailed eligibility criteria for genetic counseling. Private payers have more detailed coverage policies for both genetic services and screening with MRI in comparison to public payers. CONCLUSION: Despite clinical guidelines establishing standards for BRCA testing, we found differences in coverage policies particularly between private and public payers. Future research and policy discussions can consider how differences in private and public payer policies influence access to genetic technologies and health outcomes.